Die Pedimente im Bereich der Montes de Toledo, Zentralspanien - Fischer, Klaus (ERDKUNDE, 1974)
The pediments situated in the central and marginal parts of the Montes de Toledo, Central Spain, belong to the largest ones of the Iberian Peninsula. They have been more or less dissected since the Pleistocene. The different alluvial terraces of the Tajo and its southern tributaries between Toledo and Talavera de la Reina with their headward erosion into the dissected pediments in the foreland of the northern Montes de Toledo prove this fact. On the alluvial terraces the facies of the sediments differ from those of the rañas which cover the bedrocks not thickly but in wide areas. Pediments dated into the Pliocene are not formed by sheet flood but by landslides and mudstreams. The facies of the rañas (valley train, intensively coloured) belong, according to their pliocene origin, to the pediments and the rock-surface of the pediments with their coarse granitic sands and lead to the assumption that the traditional interpretation of pediments as characteristic forms of arid areas cannot be accepted without doubt.